Pipeline heating and cooling - Sobota Tomasz; Taler Dawid; Lubecki Szczepan (MATEC Web of Conferences, 2018)
The work aims to determine the undetermined temperature distribution of the medium and the pipeline wall using the finite difference method. Time courses of the temperature of the flowing medium and pipeline walls caused by a step change in temperature of the medium at the pipeline inlet, obtained by the numerical method, were compared with the courses calculated using strict analytical formulas. The numerical method of determining transient courses of the temperature of medium and pipeline wall can be used in the analysis of heating and cooling of heating or power pipelines with any changes in time of mass flow of the flowing medium or temperature of the medium at the inlet to the pipeline.